The Effect of Adipose-derived Mesenchymal Stem Cells on Healing of Massive Chronic Rotator Cuff Tear in Rodent Model. Issue 7 (21st July 2017) - Pauyo, Thierry; Rothrauff, Benjamin B.; Chao, Tom; Hirsch, David; Beaudry, Mason; Debski, Richard; Tuan, Rocky S.; Musahl, Volker
Objectives: Mesenchymal stem cells (MSCs) may promote restoration of the structure and function of the injured tendon-bone interface of the healing rotator cuff following repair. As compared to acute tears, chronic massive rotator cuff tears are a challenging healing microenvironment, with degenerative changes present in the muscle, tendon, and bone. Therefore, the purpose of this study was to explore the efficacy of MSCs in restoring the tendon-bone interface following repair of massive chronic rotator cuff tears in a rodent model. Methods: Adipose-derived mesenchymal stem cells (ADSCs) were isolated from inguinal fat of adult Lewis rats (n= 8) and expanded to passage 2 (P2). To induce degenerative changes in a rat modeling a massive chronic rotator cuff tear, the supraspinatus and infraspinatus tendons were transected bilaterally near their bony insertion and the corresponding muscle bellies were injected with 2.5 U botulinum toxin A (botox). Eight weeks later, tendons were repaired with or without augmentation at the tendon-bone interface. In particular, there were 5 groups ; (1) no repair (defect), (2) repair, (3) repair + fibrin, (4) repair + fibrin + ADSCs, (5) repair + fibrin + ADSCs + TGF-β3 (n=12 shoulders per condition). An equivalent cohort of animals received acute tendon transection (without botox injection) and immediate repair with or without augmentation. At 4 weeks following repair, animals were euthanized and the shoulders were harvested for analysis of bone morphometry, histology, and mechanical properties. Bone morphometry of the humeral head including; bone mineral density, bone volume percentage, and trabeculae number, thickness, and spacing was determined using micro-computed tomography. Statistical analyses included 2-way ANOVA with Tukey post-hoc tests. Analyses of histology and mechanical properties are ongoing. Results: ADSCs at P2 demonstrated a spindle-shaped morphology and were capable of forming colonies (Fig. 1A) and undergoing trilineage differentiation (Fig. 1B). Compared to healthy and acutely injured shoulders, muscles in the chronic condition exhibited atrophy, fibrosis, and fatty infiltration, with corresponding reductions in wet weights (Fig. 1C). All groups in the acute and chronic conditions possessed significantly reduced bone mineral density and bone volume percentage compared to healthy controls (p < 0.05), while only groups in the chronic condition exhibited compromised trabecular number and spacing. (p < 0.05). Augmentation of repairs with ADSCs (with or without TGF-β3) in the chronic condition significantly increased bone mineral density over defect controls (p < 0.05). Conclusion: Two-tendon transection and chemical paralysis of rotator cuff muscles in a rodent model mimics the degenerative changes seen in human shoulders, including decrements in bone quality. The efficacy of ADSCs in restoring structure and function of the tendon-bone interface likely depends on tear chronicity and size and may have greater benefit in chronic tears, as suggested by improvements in parameters of bone morphometry. This study will help further clarify the involvement of adult stem cell therapy in enhancing healing of the rotator cuff enthesis in the setting of degenerative tissue. Future studies would investigate the potential of adult stem cells to promote muscle regeneration in chronic rotator cuff tears and augment structural healing at the enthesis.